Melanin production in coelomycetous agents of black grain eumycetoma. (19th January 2021) - Lim, Wilson; Parel, Florianne; de Hoog, Sybren; Verbon, Annelies; van de Sande, Wendy W J
Abstract: Background: Eumycetoma is a fungal infection characterised by the formation of black grains by causative agents. The melanin biosynthetic pathways used by the most common causative agents of black-grain mycetoma are unknown and unravelling them could identify potential new therapeutic targets. Method: Melanin biosynthetic pathways in the causative fungi were identified by the use of specific melanin inhibitors. Results: In Trematosphaeria grisea and Falciformispora tompkinsii, 1, 8-dihydroxynaphthalene (DHN)-melanin synthesis was inhibited, while DHN-, 3, 4-dihydroxyphenylalanine (DOPA)- and pyo-melanin were inhibited in Medicopsis romeroi and Falciformispora senegalensis. Conclusion: Our data suggest that Me. romeroi and F. senegalensis synthesise DHN-, DOPA- and pyo-melanin, while T. grisea and F. tompkinsii only synthesise DHN-melanin.